Análisis reestructuración y plan de marketing del complejo deportivo “borma” de la ciudadela los vergeles. - Acuria Cagua, Diana Carolina (2009)
The restructuring and marketing plan of the Complex Borma located in the citadel the Vergeles is given from seeing the need of this Complex since if one was not giving the opportune attention to the same one it might disappear because its this infrastructure very spoiled to the point of which they have come some walls below(down) and the swimming pools are closed by the mistake of maintenance and uses of the same ones;. For which we could notice also the opportunity of business, in which in our project we will demonstrate that with a correct plan of marketing, and restructuring and the most important opening to the public because this complex is familiar(family) we will have high income, we will be known in the way since we do not have direct competitors and will recover our short-term investment. Turning into a Sports Complex that differentiates for the good service to the client, varieties of distraction and the most important thing without taking memberships since as it is done by the majority of existing complexes in the way.